Design and development of a medium scale egg grading machine - 441240 Chin, Kai Shoong (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 2001